A new method of utilising stability study results in applying out-of-step protection to allow observability of rotor angle unstable conditions - Van Eyssen, Juanita (Department of Electrical Engineering, 2016)
Power system rotor-angle unstable conditions may cause undesired operation of distance relays, resulting in the unnecessary switching of lines. To prevent the possible undesired operation of distance relays, a protection type known as out-of-step blocking is used. This protection type is complemented by another type of protection, known as out-of-step tripping protection. The tripping protection's main functions are to detect total loss of synchronism and send tripping signals to selected locations in the system to initiate islanding. In this research the application of out-of-step blocking and tripping protection was investigated. The motivation for the research was provided by system unstable incidents that occurred in Eskom, the electricity utility of South Africa. Detailed out-of-step protection investigations indicated that the out-of-step blocking and tripping protection applied according to a method which is based on an existing approach failed to detect the unstable conditions. In summary, the detailed investigations showed that the existing approach of applying out-of-step blocking and tripping protection is not adequate as it does not allow the necessary observability1 and correct detection of rotor-angle unstable conditions.